2011
DOI: 10.24039/rnh2011511030
|View full text |Cite
|
Sign up to set email alerts
|

Clinostomum Marginatum (Braun, 1899) Y Austrodiplostomum Compactum (Lutz, 1928) Metacercarias Con Potencial Zoonótico en Pygocentrus Nattereri (Kner, 1858) (Characiformes: Serrasalmidae) De La Amazonía Central, Brasil

Abstract: El presente estudio investigó la presencia de helmintos en filetes de la piraña roja, Pygocentrus nattereri (Kner, 1858), alertando sobre un posible potencial zoonótico de su consumo en la forma in natural. Fueron examinados 40 peces capturados en lagos de varzea del Río Solimões, localizados entre los Municipios de Coari y Manaus en la Amazonía Central, Brasil. Todos los peces analizados fueron adultos y presentaban quiste amarillos en la musculatura del filete. Fueron encontrados 69 quistes e identificadas l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The Moravec 1998, Pavanelli et al 2004, Thatcher 2006, Barros et al 2006, Vieira et al 2010, Morais et al 2011, Vital et al 2011, Benigno et al 2012, Cárdenas et al 2012, Vicentin et al 2013, Brito-Junior & Tavares-Dias 2018. Austrodiplostomum sp., P. (S.) inopinatus and Contracaecum sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Moravec 1998, Pavanelli et al 2004, Thatcher 2006, Barros et al 2006, Vieira et al 2010, Morais et al 2011, Vital et al 2011, Benigno et al 2012, Cárdenas et al 2012, Vicentin et al 2013, Brito-Junior & Tavares-Dias 2018. Austrodiplostomum sp., P. (S.) inopinatus and Contracaecum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although congeneric species P. nattereri is native to the Amazon and Paraná river basins, it can be found in several South American countries (Froese & Pauly 2019). Its endoparasite fauna was investigated by Rego & Eiras (1989), Rego & Pavanelli (1990), Moravec (1998), Pavanelli et al (2004), Thatcher (2006, Barros et al (2006Barros et al ( , 2010, Vieira et al (2010Vieira et al ( , 2011, Morais et al (2011Morais et al ( , 2019, Benigno et al (2012), Cárdenas et al (2012), Vicentin et al (2013) and Brito-Junior & Tavares-Dias (2018). The current study has investigated the endoparasite fauna of fish species P. piraya because the few studies carried out on this topic (Travassos et al 1928, Moreira et al 1994, Brasil-Sato 2003, Moravec et al 2008, Santos et al 2009, Monteiro et al 2016) have indicated that this piranha species is a potential host for peculiar endoparasite fauna in Três Marias reservoir, upper São Francisco river, state of Minas Gerais, Brazil.…”
Section: Introductionmentioning
confidence: 99%